Zimbabwe : A Preliminary Review of Parastatals - Altana, Daniel; Kojo, Naoko C. (World Bank, Washington, DC, 2015)
This paper reviews the performance of the parastatal sector, with a specific focus on four main parastatals: the Zimbabwe Electricity Supply Authority (ZESA); the Zimbabwe Water Authority (ZINWA); the National Oil Company of Zimbabwe (NOCZIM); and the Grain Marketing Board (GMB). These parastatals are selected on the basis of their quasi-fiscal dependency and strategic importance to the economy. The specific objective of this paper is to identify the important factors behind their eroding profitability as observed in their financial statements, and make some preliminary thoughts about the way forward. This paper was prepared based on the data provided to a World Bank team, supplemented by information collected through interviews with the representatives of parastatals, the RBZ, the Ministry of Finance, line ministries and the private sector in November 2007. The statistics presented in this paper should be interpreted with extreme caution. As prices are heavily distorted in the presence of extremely high inflation and pervasive price controls, analysis of quasi-fiscal data and parastatals’ financial performance has posed a significant challenge to the team. While every possible effort was made to address such distortions, analysis largely based on annual data cannot possibly capture a fully accurate picture, and should therefore be taken with caution.